2019
DOI: 10.1002/dmrr.3126
|View full text |Cite
|
Sign up to set email alerts
|

Association of high circulating testosterone with increased glycaemic variability in type 2 diabetes: A cross‐sectional study in China

Abstract: Background: Testosterone affects insulin resistance, but the effect of testosterone treatment on type 2 diabetes (T2D) remains controversial. We aimed to investigate the association between circulating total testosterone (TT) and glycaemic variability using continuous glucose monitoring (CGM) in patients with T2D. Methods:A total of 248 men with T2D were enrolled in the study. Clinical characteristics and plasma for glycated haemoglobin (HbA1c) and C-peptide assessment were collected. TT was measured using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The mechanism remains unclear (6). We previously reported that testosterone levels were significantly lower in men with T2DM using metformin than in men not using metformin in a cross-sectional study (7).…”
mentioning
confidence: 96%
“…The mechanism remains unclear (6). We previously reported that testosterone levels were significantly lower in men with T2DM using metformin than in men not using metformin in a cross-sectional study (7).…”
mentioning
confidence: 96%
“…The authors found no significant differences in TIR, time above range (TAR, > 140 mg/dL), time below range (TBR, < 70 mg/dL), estimated HbA1c, area under the curve (AUC) for blood glucose values above and below the target during the intervention period. A previous study conducted by Ding et al speculated that increasing testosterone levels in hypogonadal men with DM could lead to an increase in glycemic variability after TRT [ 36 ], but the analysis of data from a the CGM highlighted no significant deterioration of any parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Our sample size calculation was based on our previous cross-sectional study [27]. Acarbose was used by 32 of 248 patients.…”
Section: Methodsmentioning
confidence: 99%